Sons do Porto: para uma cartografia sónica da cidade vivida - Guerra, Paula (2018)
This article has its focus on an exploratory research on the positioning of the city of Porto under the perspective of the strength of the structure of the production chain involved in the circulation of its musical production, considering the dialogical relationship between territorialities and music. In this study, the concept of "music scenes", "creative cities" and "musical cities" will be debated, based on an analysis of the sociotechnical network (Latour, 2012) of the musical industry (in all its segments) in the city of Porto in Portugal. The methodology involved is a bibliographical review about the revisiting and re-alignment of the concept of music scene and the monitoring of activities performed in the city, reanalyzing and mapping the survey of resources and musical assets in 2008 (Guerra, 2013 and 2010).